1994
DOI: 10.1128/aac.38.10.2346
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of rifabutin alone or in combination with isoniazid in preventive therapy of mouse tuberculosis

Abstract: The ever-increasing incidence of tuberculosis calls for the implementation of control measures, including new efficient, short-term preventive therapies to replace 6 to 12 months of isoniazid therapy. The efficacies of 12-week regimens of rifabutin or isoniazid given daily and the combination of the two drugs administered intermittently were evaluated in mice infected with Mycobacterium tuberculosis after vaccination with the bacillus Calmette-Guerin (BCG) to imitate some features of the natural infection in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…Therapy of MAC-infected mice with RBT (or, in some studies, with RPT) in combination with either EB, CFZ, AZM, KM, EBϩCFZ, CAMϩEB, or CFZϩKM was more effective than that with each drug alone. 86,102,105,107 As indicated in Table 6, in clinical studies, RBT was effective against intractable TB and MAC infections (positive response, 8% to 92%). [88][89][90]109,110 Efficacy was achieved with certain regimens involving RBT (RPT) in combination with other drugs, including EB, CFZ, CAM, INH, and CPFX.…”
Section: New Macrolidesmentioning
confidence: 93%
See 1 more Smart Citation
“…Therapy of MAC-infected mice with RBT (or, in some studies, with RPT) in combination with either EB, CFZ, AZM, KM, EBϩCFZ, CAMϩEB, or CFZϩKM was more effective than that with each drug alone. 86,102,105,107 As indicated in Table 6, in clinical studies, RBT was effective against intractable TB and MAC infections (positive response, 8% to 92%). [88][89][90]109,110 Efficacy was achieved with certain regimens involving RBT (RPT) in combination with other drugs, including EB, CFZ, CAM, INH, and CPFX.…”
Section: New Macrolidesmentioning
confidence: 93%
“…86,[102][103][104][105][106][107][108] First, RBT displayed appreciable therapeutic efficacy against murine infections caused by MTB and MAC. RBT exhibited potential efficacy in the prophylaxis of tuberculosis in mice.…”
Section: New Macrolidesmentioning
confidence: 99%
“…First, a prospective, randomized, double-blind study showed that once-weekly RPT (600 mg) with INH (900 mg) was safe and effective for the treatment of pulmonary TB in HIV-negative people without cavitation on chest radiography and the rate of failure/relapse in this regimen (2.9%) was in the same level as that in twice-weekly RIF plus INH (2.5%) [131]. In addition, a subsequent study by Bock et al showed that the rate (4 %) of discontinuation of therapy for any reason and adverse events on once-weekly Jabes (1994), Kelly (1996), , Brooks (1998), Miyazaki (1999), Keung (1999), Lenaerts (1999), Daniel (2000), Weber (2001) continuation phase therapy with RPT (900 mg) plus INH did not increase, compared to that (6%) of once-weekly RPT (600 mg) plus INH [132]. This study suggested that RPT at 900 mg dose may be suitable for continuation phase treatment of TB.…”
Section: Rifabutin and Rifapentinementioning
confidence: 97%
“…(1) RBT and RPT exhibit strong therapeutic efficacies in the order RBT, RPT > RIF, when given daily to infected mice [118,122]. In addition, RBT exhibits potent efficacy in prophylaxis of TB in mice.…”
Section: Rifabutin and Rifapentinementioning
confidence: 98%
See 1 more Smart Citation